Gaussian bi-periodic Fibonacci and Gaussian bi-periodic Lucas sequences - Uygun, Sukran (Sigmae, 2021)
In this study, we bring into light of the gaussian bi-periodic Fibonacci and gaussian bi-periodic Lucas sequences. The Binet formula as well as the generating function for these sequences are given. The convergence property of the consecutive terms of this sequence is examined after which the well known Cassini, Catalan and the D'ocagne identities as well as some related summation formulas are also given.